Preliminary near wall hemodynamic evaluation of a coronary artery bypass graft model with a flow streamlining implant - Pedroso, Pedro D.; Hershey, Bradley L.; Anayiotos, Andreas (My University, 2002)
Coronary artery disease (CAD) is the leading cause of death in the world today. According to the American Heart Association 529,659 people in 1999 died as a result of CAD [1]. Starting in the 1960’s, surgeons have used Coronary Artery Bypass Graft (CABG) techniques in order to reestablish blood flow to the heart. Today, the procedure remains the same, using autologous grafts, such as the mammary artery and the saphenous vein. An unresolved problem, is that a significant number of CABGs reocclude months to years postoperatively. In the case of Saphenous Vein Grafts (SVGs) typically 50% of these bypasses are totally occluded months to years after the procedure, the remaining half being more than 50% occluded [2]. The re-occlusion of CABGs is due to a process labeled intimal hyperplasia (IH). Investigators have shown that IH, believed by some to be a remodeling process, occurs at branch sites, regions of curvature, and anastomotic junctions [3,4]. At these sites there are low residence times, slow secondary structures, disturbed flow, and areas of recirculation, therefore the onset of IH is believed to be hemodynamically linked. Most recently, floor IH has been attributed to four variables: time averaged wall shear stress (WSS), oscillating shear index (OSI), spatial wall shear stress gradients (WSSG), and temporal WSSG [5]. Adverse values of these parameters, in the case of SVGs, are believed to be caused by impedance mismatch at the anastomosis site. Over time this characteristic causes a bulge at the sinus. Such a morphology additionally contributes to disturbed flows which tend to propagate down the CABG and are believed to play a major role in the development of IH and the eventual failure of the graft.
Keywords: Coronary artery bypass; Hemodynamics; Surgeons